A base industrial de defesa brasileira - José Carlos Albano do Amarante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– In this work, it is pointed out that the demand scenario of military means have been suffering from the influence of electronics, such as in the case of basic technology. In this context, there are four ways to make contemporary war: robotics, automation, systemic and cybernetics. It is shown the defining aspects of military equipment priority, associated with: the cybernetic war; the cycle of technological functions of combat; the operation with electromagnetic radiation; and the properties of the robotics and automation. Inspired by the above conditions, a defense industry (ID) will probably have the best deals. It discusses the Brazilian Defense Industrial Base (BID), structurally integrated by five key pillars: the scientific, the technological, the infrastructural, the industrial and the logistical. It is shown, also, that the BID is composed of different public and private institutions, being responsible for the development, production and logistics of military technology. The operation of the modern BID is described, emphasizing the military innovation, the Science, Technology & Innovation System of Defense Interest (SisCTID) and the civil-military technological duality. It studies specifically the ID, fundamental element of the BID, and proposes the ideal model of a ID, through the establishment of performance indicators in technical, industrial and structural-administrative fields. It discusses the modern industrial mobilization, based on the activation of the BID. It evaluates relevant aspects of contemporary planning for the effective supply of the Armed Forces with military means. Differentiated attitudes are proposed for when the objective is to reach immediate, mediate and distant capacity. Finally, it discusses the role of the National Strategy for Defense (END) as catalytic agent of deterrence.
Keywords: H56; L64; O32; 330; defense industrial base; defense industry; supplies; mobilization; iceberg of the defense industrial base; Rüstungsindustrie; Brasilien